Pengaruh Metode Drill Terhadap Kemampuan Menulis Karangan Deskripsi Siswa di SD Negeri 81 Palembang - Dewi, Shanti; Hermansah, Bambang; Ayurachmawati, Puji (Institut Teknologi Pendidikan Indonesia, 2022)
This study discusses the effect of using the drill method (practice) on the ability to write descriptive essays for fourth grade students at SD Negeri 81 Palembang. The purpose of this study was to determine the effect of using the drill method (practice) on the ability to writedescriptive essays for fourth grade students. The type of research used is Quasi Experimental and the research method used by the researcher is quantitative. The type of design used in this study is